Correlation study of shallow layer rock and soil thermal physical tests in laboratory and field. (January 2015) - Gao, Ping; Zhang, Yanjun; Yu, Ziwang; Fang, Jingtao; Zhang, Qing
Highlights: The primary factors that influence thermal physical parameters were chosen. AHP was used to determine the weights of every factor. Modified laboratory test could fully reflect the heat transfer capacity. The modified method provided a good supplement for in situ TRT. Abstract: A new method was proposed in this study to determine the correlation between laboratory and thermal response tests that are usually applied to examine the thermal physical parameters of shallow-layer rock and soil. Layer depth, water content, density, and permeability were found to be the primary factors that affect the discrepancy between the two tests. Analytic hierarchy process was then used to compute the weighted values of each factor, and the testing results of the thermal physical parameters in the laboratory were modified based on the weighted values. Field and modified laboratory thermal physical parameters and practical heat transferring process were simulated using the numerical model, and the discrepancies in the heat conduction capacity were similar under three conditions. Finally, the product of pipe depth and thermal conductivity was suggested to represent heat transfer capacity, and the computed uniform thermal conductivity of the laboratory after modification was proposed to be basically equal to the comprehensive thermal conductivity of the thermal response test. This study provides new insights in determining the thermal physical parameters of rock and soil layers.